The Influence of Youtube Beauty Vloggers on Cosmetic Consumer Decisions with User Generated Content as A Moderating Variable - Anggi Oktawiranti; Raditya Suksmaneng Daru; Gusti Noorlitaria Achmad; Asnawati Asnawati; Saida Zainurossalamia ZA (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research is a quantitative study with an explanatory approach, an approach that places previous research as a mainstay for creating, modifying, and proving the hypotheses in this article. The data used in this study is primary data obtained by the researcher from one hundred and fifty consumers of Athena and MAXI cosmetics spread throughout Indonesia. The data obtained was analyzed using the smart PLS 4.0 analysis tool. The conclusion in this article show that the hypothesis that the researcher formulated in this article, namely the YouTube Beauty Vlogger variable can have a positive relationship direction and a significant influence on Cosmetic Consumer Decisions and the User Generated Content variable can also moderate the influence of the YouTube Beauty Vlogger variable on Cosmetic Consumer Decisions. From the first row above, it shows that the first hypothesis in this article can be accepted because the P-Values ​​value is positive and is below the 0.05 significance level, namely 0.014. These results indicate that YouTube Beauty Vlogger can make products more famous, wider market share, and increasing demand for cosmetic products. In addition, the second hypothesis in this article can also be accepted because the same thing is the P-Values ​​value is positive and below the 0.05 significance level. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven.